Faktor-faktor yang Berhubungan dengan Fatigue Pada Masinis PT. Kereta Api Indonesia Daerah Operasional 3 Cirebon - Amaliyah, Citra; Ramdhan, Doni Hikmat Hikmat (National Journal of Occupational Health and Safety, 2021)
Fatigue is a significant factor regarding safety issues such as transportation incidents and errors. As a part of land transportation, safety has also become an issue in the railway industry. In 6 years, there have been at least 700 extraordinary incidents in the railway industry in Indonesia, including train collisions. From the National Transportation Safety Committee investigation report, it was also found that several cases of train crashes occurred due to train drivers’ fatigue. Therefore, this study aims to determine the level and the factors associated with fatigue in train drivers. This research was conducted in January – June 2021 at PT. Kereta Api Indonesia Operational Area 3 Cirebon is one of the strategic, operational areas and a place of train driver exchange. This research is quantitative research with a cross-sectional study design. The samples in this study were 144 drivers of passenger and freight trains. The data are analyzed by a chi-square statistical test. The results of the study showed that 45.8% of respondents experienced mild fatigue, and 54.2% of respondents experienced moderate fatigue. From this study, it is also known that there is a relationship between BMI (OR1 = 2,454; OR2 = 4,723), sleep duration (OR = 2,120) and work environment (OR = 3,495) with fatigue in train driver. For this reason, companies need to optimize health promotion for train drivers with abnormal nutritional status, ensure driver rest periods and install air conditioning in the cabin to reduce temperature and noise that have an impact on fatigue.